A remark on the approximate fixed-point property. (30th January 2003) - Kuczumow, Tadeusz
Abstract : We give an example of an unbounded, convex, and closed setC in the Hilbert spacel 2 with the following two properties: (i)C has the approximate fixed-point property for nonexpansive mappings, (ii)C is not contained in a block for every orthogonal basis inl 2 .